The Analysis Of Parental Participation In Improving Children's Learning Motivation During The Covid-19 Pandemic - EL-Taro, Erra; Aryani, Maria Lilis (Universitas Sebelas Maret, 2022)
Covid-19 has hit many countries in the world, including Indonesia. This epidemic has affected many sectors of life, including the education sector. The government's rules regarding the Implementation of Learning from Home is one of their effort to reduce the spread of Covid-19. In this regard, teachers and parents have involvement in increasing the children's learning motivation. This research raised parental participation in providing learning motivation to students during Distance Learning. The method used in this research is the literature review and survey method. The researcher used several reference books and questionnaires with the type of scale being differential semantic that had the highest score is five and the lowest score is one. The result of this research is the participation of parents in providing learning motivation to students during distance learning consists of three aspects: facilities, time, and child psychology. The percentage of the role of parents in motivating children in the aspect of facilities is 94.78%; in time aspect is 97.68%, and in the psychology of children aspect is 94.78%. So, most parents in grades V and VI have tried to increase learning motivation in distance learning during a pandemic.